Innovative Approaches to Seaweed Farming: The Case of Tesabela Village, West Kupang, East Nusa Tenggara, Indonesia - Pratiwi, Rifqah; Amalo, Pieter; Ni Putu, Dian Kusuma; Serihollo, Lukas G.G. (PT Larva Wijaya Penerbit, 2025)
The coastal community of Tesabela Village, West Kupang, East Nusa Tenggara, predominantly practices traditional seaweed farming methods, such as longline and off-bottom techniques, which limit production efficiency due to environmental challenges and lack of advanced technological knowledge. This study evaluates and disseminates innovative solutions, including Kajarula Technology, Biorula Biofertilizer, Rula Basket, and Selvarula (Selection of Seaweed Varieties). These innovations address critical issues such as sedimentation, pest disruptions, and suboptimal seaweed growth caused by inadequate farming methods and environmental conditions. Community engagement activities from July to October 2023 involved participatory training sessions, production assistance, and the distribution of farming inputs, benefiting 50 participants, including farmers, academics, and local leaders. The implementation of Selvarula was particularly suited for the local shallow water environment, offering a sustainable, cost-effective approach to improve productivity and seed quality. Results highlight the potential of integrating these technologies to empower the community through knowledge transfer, improved production methods, and economic resilience. This initiative underscores the importance of collaborative efforts between academia and local communities in fostering sustainable development in coastal areas.